The role of crowdsourcing on digital transformation and operational performance in African financial services - Nayer, Vishal (University of the Witwatersrand, Johannesburg, 2024)
This research scrutinises the influence of Crowdsourcing (CS) in propelling Digital Transformation (DT) and bolstering Operational Performance (OP) within African Financial Service Providers (FSPs). While CS merges outsourcing, social networking, and mass collaboration to utilise a wide pool of intellect for complex problem-solving, its integration in DT is crucial for FSPs to harness global insights and expertise. In Africa, DT is lagging, primarily due to low Digital Maturity (DM), restricted technology access, and cultural resistance. This study addresses these impediments by examining the role of CS in expediting DT and its subsequent effect on OP. The research methodology entailed semi-structured interviews with 15 stakeholders in the industry, involving CEOs, CTOs, and Senior Managers. Data was analysed using AtlasTi software, ensuring credible, informed conclusions through thematic analysis and triangulation with secondary sources. Although the qualitative nature of this study limits its generalisability, it provides an intensive exploration of CS as a catalyst for DT and OP enhancement in the sector. Findings illuminate CS's pivotal role in the digital evolution of African FSPs, presenting a strategic path to overcome digital maturation challenges and stay competitive. The study's theoretical underpinnings are based on the Diffusion of Innovation theory, positioning CS as an instrument for disseminating new ideas and practices vital for achieving OP in the digital era. It offers a strategic framework for FSPs to navigate digital maturity, access challenges, and cultural resistance. Ultimately, the study outlines how CS can be harnessed to accelerate the adoption of DT initiatives, thus refining operational efficiency, and securing a competitive edge in a dynamically shifting industry landscape.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Crowdsourcing; Digital Maturity; Digital Transformation; Operational Performance; UCTD; SDG-8: Decent work and economic growth